BUSINESS PROCESS REENGINEERING: CONCEPTS CAUSES AND EFFECT - Bernardo Nugroho Yahya (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2002)
Some people made a wrong concept about Business Process Reengineering (BPR). Some were misunderstanding about the BPR term. In other way, so many researches were introduced to describe a better definition about BPR. The thinking about concepts, causes, and effect of BPR will make a new perception about the term of BPR itself as a better methodology instead of the other Quality Management Methodology such as Total Quality Management (TQM), Just In Time (JIT), etc. This paper will mention the context of BPR in some of case study's journal.